Simple and robust 3D bioprinting of full-thickness human skin tissue. Issue 4 (1st April 2022) - Liu, Jing; Zhou, Zhengtong; Zhang, Min; Song, Feng; Feng, Chong; Liu, Haochen
ABSTRACT: Artificial skins have been used as skin substitutes for wound healing in the clinic, and as in vitro models for safety assessment in cosmetic and pharmaceutical industries. The three-dimensional (3D) bioprinting technique provides a promising strategy in the fabrication of artificial skins. Despite the technological advances, many challenges remain to be conquered, such as the complicated preparation conditions for bio-printed skin and the unavailability of stability and robustness of skin bioprinting. Here, we formulated a novel bio-ink composed of gelatin, sodium alginate and fibrinogen. By optimizing the ratio of components in the bio-ink, the design of the 3D model and the printing conditions, a fibroblasts-containing dermal layer construct was firstly fabricated, on the top of which laminin and keratinocytes were sequentially placed. Through air-liquid interface (ALI) culture by virtue of sterile wire mesh, a full-thickness skin tissue was thus prepared. HE and immunofluorescence staining showed that the bio-printed skin was not only morphologically representative of the human skin, but also expressed the specific markers related to epidermal differentiation and stratum corneum formation. The presented easy and robust preparation of full-thickness skin constructs provides a powerful tool for the establishment of artificial skins, holding critical academic significance and application value. Graphical Abstract: uf0001